Relationship of constipation and autonomic neuropathy in patients with non-insulin dependent diabetes mellitus and the effects of cisapride on colonic transit time - M. Emin ÖNDE; A. Kemal GÜRBÜZ; Levent DEMİRTÜRK and Ergun KOÇER and Mesut BAŞAK and Hayati TOR (Turkish Journal of Gastroenterology, 2019)
-